2008
DOI: 10.1590/s0101-81752008000300009
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of diversity and abundance of fungus-growing ants (Formicidae: Attini) in areas of the Brazilian Cerrado

Abstract: Fungus-growing ants (tribe Attini) are characteristic elements of the New World fauna. However, there is little information on the patterns of diversity, abundance, and distribution of attine species in their native ecosystems, especially for the so-called "lower" genera of the tribe. A survey of attine ant nests (excluding Atta Fabricus, 1804 and Acromyrmex Mayr, 1865) was conducted in a variety of savanna and forest habitats of the Cerrado biome near Uberlândia, Brazil. In total, 314 nests from 21 species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Several studies, including previous studies in the Cerrado, have already demonstrated that many ant species have strong habitat associations and that, as consequence, there is often a high degree of species turnover between different habitats (Bestelmeyer and Wiens 2001;Ribas et al 2003;Vasconcelos and Vilhena 2006;Ribas and Schoereder 2007;Vasconcelos et al 2008). However, very few studies have assessed the relative contribution of alpha and beta diversity to regional ant diversity (gamma diversity) (but see Dahms et al 2010;Paknia and Pfeiffer 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, including previous studies in the Cerrado, have already demonstrated that many ant species have strong habitat associations and that, as consequence, there is often a high degree of species turnover between different habitats (Bestelmeyer and Wiens 2001;Ribas et al 2003;Vasconcelos and Vilhena 2006;Ribas and Schoereder 2007;Vasconcelos et al 2008). However, very few studies have assessed the relative contribution of alpha and beta diversity to regional ant diversity (gamma diversity) (but see Dahms et al 2010;Paknia and Pfeiffer 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the Cerrado suggest that it supports a highly diverse ant fauna (Silva et al 2004;Lopes and Vasconcelos 2008), including poorly known, rare, and endemic species (Brandão et al 2001;Vasconcelos et al 2008;Solomon et al 2011). These studies also indicate a high degree of species turnover among habitats, especially among major plant physiognomies (Vasconcelos and Vilhena 2006;Lopes and Vasconcelos 2008;Vasconcelos et al 2008). Therefore, it may well be possible that local variations in vegetation cover could promote an increase in ant diversity at higher scales as also predicted by the mosaic concept (Whittaker and Levin 1977).…”
Section: Introductionmentioning
confidence: 90%
“…As habitats are altered due to logging, clearing for agriculture, or climate change, such alterations are likely to induce changes in ant species composition (cf. Vasconcelos et al 2008) impacting ant species diversity through either species composition changes and/or species loss.…”
Section: Anthropogenic Effectsmentioning
confidence: 99%
“…We focused our study on ants because they are highly abundant in tropical ecosystems, play many ecological roles (including the control of populations of other insects), and are responsive to various types of land clearance and conversion across a wide range of habitats (Underwood & Fisher 2006). Furthermore, previous studies in the Cerrado have revealed a highly diverse ant fauna (Silva et al 2004, Lopes & Vasconcelos 2008, which includes poorly known, rare, and endemic species (Brandão et al 2001, Vasconcelos et al 2008a, Solomon et al 2011.…”
mentioning
confidence: 99%